Development of an Innovative Seat Reservation System for University Buildings Based on BIM Technology - García-Granja, M. J.; Blázquez-Parra, Elidia Beatriz; Cimadomo, Guido; Guzmán-Navarro, Francisco (MDPI, 2022)
The usefulness of building information modeling (BIM) for facilities management, although widely demonstrated, has not been extended to use management in university spaces. In public facilities with free access, it is uncommon to be able to check the availability of seats, which causes capacity problems. In addition, while several studies show that the use of BIM makes the graphic communication of useful information about buildings more attractive and intuitive for its users, there are still challenges regarding how to make it accessible to the public, taking into account their preferences. The purpose of this study is to demonstrate the benefits of implementing BIM in a real-time seat occupancy management system to enable reservations tailored to the user’s needs by offering various means of consulting model information. The research method focuses on the utility model designed for a university library in Malaga, Spain. The results, based on data obtained from a survey, indicate that users positively assessed the quality of the information offered, showed great interest in its use, and also considered it comparatively superior to other reservation systems used. The Results and Discussion and Conclusions sections also show the potential of the system to control social distancing and energy expenditure.
Keywords: Universidades - Control de acceso; Reservation system; Building information modeling; Facility management; University library; Visualization